Yaroslavl State Medical University on the Threshold of 75th Anniversary - A. V. Pavlov (Высшее образование в России)
In 2019 Yaroslavl State Medical University celebrates its 75th anniversary. For decades, the university has held strong positions in the educational and scientific space of modern Russia. Well-known scientists, health care managers, highly decorated experts in various branches of medicine and prominent public figures are among the alumni of the University. Today, Yaroslavl State Medical University provides training for highly qualified medical workers, as well as professional retraining and advanced training of doctors and pharmacists, actively carries out basic and applied research, develops modern information and technological tools and introduces innovative teaching models. The article examines the modern features of the organization of the educational process and the practical training of students, extracurricular work, research and innovation activities, inter university interaction and international cooperation, and also formulates the main prospects for the development of the University.